Overproduction of Phospholipids by the Kennedy Pathway Leads to Hypervirulence in Candida albicans - Tams, Robert N.; Cassilly, Chelsi D.; Anaokar, Sanket; Brewer, William T.; Dinsmore, Justin T.; Chen, Ying-Lien; Patton-Vogt, Jana; Reynolds, Todd B. (Frontiers in Microbiology, 2019)
Candida albicans is an opportunistic human fungal pathogen that causes life-threatening systemic infections, as well as oral mucosal infections. Phospholipids are crucial for pathogenesis in C. albicans, as disruption of phosphatidylserine (PS) and phosphatidylethanolamine (PE) biosynthesis within the cytidine diphosphate diacylglycerol (CDP-DAG) pathway causes avirulence in a mouse model of systemic infection. The synthesis of PE by this pathway plays a crucial role in virulence, but it was unknown if downstream conversion of PE to phosphatidylcholine (PC) is required for pathogenicity. Therefore, the enzymes responsible for methylating PE to PC, Pem1 and Pem2, were disrupted. The resulting pem1∆/∆ pem2∆/∆ mutant was not less virulent in mice, but rather hypervirulent. Since the pem1∆/∆ pem2∆/∆ mutant accumulated PE, this led to the hypothesis that increased PE synthesis increases virulence. To test this, the alternative Kennedy pathway for PE/PC synthesis was exploited. This pathway makes PE and PC from exogenous ethanolamine and choline, respectively, using three enzymatic steps. In contrast to Saccharomyces cerevisiae, C. albicans was found to use one enzyme, Ept1, for the final enzymatic step (ethanolamine/cholinephosphotransferase) that generates both PE and PC. EPT1 was overexpressed, which resulted in increases in both PE and PC synthesis. Morever, the EPT1 overexpression strain is hypervirulent in mice and causes them to succumb to system infection more rapidly than wild-type. In contrast, disruption of EPT1 causes loss of PE and PC synthesis by the Kennedy pathway, and decreased kidney fungal burden during the mouse systemic infection model, indicating a mild loss of virulence. In addition, the ept1∆/∆ mutant exhibits decreased cytotoxicity against oral epithelial cells in vitro, whereas the EPT1 overexpression strain exhibits increased cytotoxicity. Taken altogether, our data indicate that mutations that result in increased PE synthesis cause greater virulence and mutations that decrease PE synthesis attenuate virulence.